As dificuldades da reforma tributária como um jogo de elites na visão das elites pernambucanas - Silva, Ricardo Guimarães da (2010)
This text is focuses on the topic of Tax Reform and, in particular, its difficulty to be approved by the Congress. As the Tax System is the basis of the maintenance of federalism, since without the sharing of tax revenues among the federal entities, there is no possibility to ensure their financial independence and thus also their autonomy, the federal context is presented as an obstacle, since Reform, besides looking forward to approaching the current Tax System to an ideal system, must seek to maintain a minimum autonomy of the mentioned entities, in order that the Federal Government system - an unchangeable rule of our Constitution - does not become Unitarian. In this context, the relationship among the Federal Executive, the State Executive and the National Congress, with respect to the approval of matters concerning the agenda of the Tax Reform, is of crucial importance to understand the obstacles that have led to the shutdown of the main projects related to that subject. It seems also important to understand the interplay among elites that results on substantial changes of such proposals and that occurs inside and outside the Congress. In this sense, rational choice theory proves to be a suitable tool to help this understanding. To reach the goal of this study – which is to list the obstacles that have prevent the success of projects aimed to promote comprehensive reform in the Brazilian Tax System - 28 interviews were held. The basic requirements to select the group to be interviewed were: to exercise their activities in the State of Pernambuco, and to have participated directly or indirectly in processes of Tax Reform, in particular the proposal that was presented in 2008 and turned out to be the PEC 233/08. We interviewed former ministers, former governors, former secretaries and secretaries of revenue of the three spheres of power, federal deputies, business leaders, governmental agencies and entities’s presidents or leaders, tax lawyers and agents of the state treasure. The results suggest that, although there are several obstacles very difficult to overcome and that they must be solved and discussed during the negotiations that should take place before the proposal will be sent to the Congress, the distributive conflict among the federal entities appears to be itself as the main problem to be observed. And this problem seems to be able to dissolve – or not to respect - the arrangements made concerning the political parties – coalitions of support and opposition to the Government. And this situation has the power to chance the main 'actors' in the process of negotiation related with these kind of matters. Therefore, the negotiations will happen involving only the Federal and the State Executives and no longer the Federal Executive and its coalition of support, as it normally occurs.